Hydrophilic 3D interconnected network of bacterial nanocellulose/black titania photothermal foams as an efficient interfacial solar evaporator - Nabeela, Kallayi; Thorat, Meghana; Sumina, N. B.; Ramachandran, Animesh M.; Thomas, Reny Thankam; Preethikumar, Gopika; Mohamed, A. Peer; Asok, Adersh; Dastager, Syed Gulam; Pillai, Saju (ACS Applied Bio Materials, 2021)
The design and development of scalable, efficient photothermal evaporator systems that reduce microplastic pollution are highly desirable. Herein, a sustainable bacterial nanocellulose (BNC)-based self-floating bilayer photothermal foam (PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b) is designed that eases the effective confinement of solar light for efficient freshwater production via interfacial heating. The sandwich nanoarchitectured porous bilayer solar evaporator consists of a top solar-harvesting blackbody layer composed of broad-spectrum active black titania (BT) nanoparticles embedded in the BNC matrix and a thick bottom layer of pristine BNC for agile thermal management, the efficient wicking of bulk water, and staying afloat. A decisive advantage of the BNC network is that it enables the fabrication of a lightweight photothermal foam with reduced thermal conductivity and high wet strength. Additionally, the hydrophilic three-dimensional (3D) interconnected porous network of BNC contributes to the fast evaporation of water under ambient solar conditions with reduced vaporization enthalpy by virtue of intermediated water generated via a BNC–water interaction. The fabricated PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b is found to yield a water evaporation efficiency of 84.3% (under 1054 W m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2) with 4 wt % BT loading. Furthermore, scalable PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b realized a water production rate of 1.26 L m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2 h<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1 under real-time conditions. The developed eco-friendly BNC-supported BT foams could be used in applications such as solar desalination, contaminated water purification, extraction of water from moisture, etc., and thus could address one of the major present-day global concerns of drinking water scarcity.

Tailored synthesis of ultra-stable Au@Pd nanoflowers with enhanced catalytic properties using cellulose nanocrystals - Hakkeem, Hasna M. Abdul; Babu, Aswathy; Shilpa, Nagaraju; Venugopal, Adithya A.; Mohamed, A. P.; Kurungot, Sreekumar; Pillai, Saju (Carbohydrate Polymers, 2022)
A green strategy for the synthesis of bimetallic core-shell Au@Pd nanoflowers (NFs) employing banana pseudostem-derived TEMPO-oxidized cellulose nanocrystals (TCNC) as both capping and shape-directing agent via seed-mediated method is presented. Flower-like nanostructures of Au@Pd bound to TEMPO-oxidized cellulose nanocrystals (TCNC-Au@Pd) were decorated on amino-functionalized graphene (NH2-RGO) without losing their unique structure, allowing them to be deployed as an efficient, reusable and a green alternative heterogeneous catalyst. The decisive role of TCNC in the structural metamorphosis of nanoparticle morphology were inferred from the structural and morphology analyses. According to our study, the presence of -OH rich TCNC appears to play a pivotal role in the structured evolution of intricate nanostructure morphology. The feasibility of the bio-supported catalyst has been investigated in two concurrently prevalent model catalytic reactions, namely the oxygen reduction reaction (ORR) and the reduction of 4-nitrophenol, the best model reactions in fuel cell and industrial catalytic applications, respectively.
Keywords: Au@Pd; catalysis; Cellulose nanocrystals; Nanoflowers; oxygen reduction reaction